Legal Protection Regarding Intellectual Property Rights - Dwirainaningsih, Yustiana; Kusuma Putra, Rengga; M.Haikal Hadiyatullah (Yayasan Meira Visi Persada, 2025)
Intellectual Property Rights (IPR) are rights that provide official protection to creators and inventors for their unique and creative works. Indonesian law regulates IPR, including patents, copyrights, trademarks, industrial designs, trade secrets, and geographical indications. Each type of IPR has distinct characteristics and protections, aimed at enabling rights holders to receive fair financial compensation and recognition for their works. Law No. 28 of 2014 on Copyright protects works of art, literature, and science; Law No. 13 of 2016 on Patents protects inventions in the field of technology; and Law No. 20 of 2016 on Trademarks and Geographical Indications protects distinctive signs for goods or services. In addition, there is also a comprehensive set of laws for various types of intellectual property regulated by Law No. 31 of 2000 on Industrial Designs, Law No. 30 of 2000 on Trade Secrets, Law No. 32 of 2000 on Integrated Circuit Layout Designs, and Law No. 29 of 2000 on Plant Variety Protection. These legal provisions not only ensure the protection of individual rights but are also aimed at fostering creativity and innovation in Indonesia.